Test Methods and Specification Criteria for Mineral Filler Used in Hot-Mix Asphalt - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 357: Test Methods and Specification Criteria for Mineral Filler Used in Hot-Mix Asphalt summarizes the key findings of a project that identified test methods for mineral filler that characterize its physical and chemical effects on the performance of mastics and hot-mix asphalt. The project also explored proposed specification criteria for mineral filler that help optimize hot-mix asphalt performance.The contractor’s final report, which is summarized by NCHRP RRD 357, is available online.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Mineral and Quarry Byproducts, Volume 4 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Mineral and Quarry Byproducts, Volume 4 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of mineral and quarry byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Summary Report, Volume 1 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Summary Report, Volume 1 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of recycled materials and industrial byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Airport Participation in Oil and Gas Development - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 87: Airport Participation in Oil and Gas Development provides airports with practical considerations and responses involving oil and gas extraction. The report documents lessons learned as energy prices went from their highest levels (in the mid-2000s) to some of their lowest (in 2015 and 2016). It includes a compilation of federal, state, and local regulatory frameworks; available airport oil and gas leases; municipal permits and ordinances; and case examples from targeted interviews with eight airports. As the price of oil and gas has a long history of volatility, a view of the full price cycle has particular utility to airports.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Manufacturing and Construction Byproducts, Volume 8 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Manufacturing and Construction Byproducts, Volume 8 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of manufacturing and construction byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Non-Coal Combustion Byproducts, Volume 3 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Non-Coal Combustion Byproducts, Volume 3 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of non-coal combustion byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Coal Combustion Byproducts, Volume 2 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Coal Combustion Byproducts, Volume 2 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of coal combustion byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Slag Byproducts, Volume 5 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Slag Byproducts, Volume 5 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of slag byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition Waste, Volume 6 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition Waste, Volume 6 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of reclaimed asphalt pavement, recycled concrete aggregate, and construction demolition waste and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Recycled Materials and Byproducts in Highway Applications—Scrap Tire Byproducts, Volume 7 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 435: Recycled Materials and Byproducts in Highway Applications—Scrap Tire Byproducts, Volume 7 summarizes the results of a project that describes the experiences of transportation agencies in determining the relevant properties of scrap tire byproducts and the beneficial use for highway applications.NCHRP Synthesis 435 is presented in eight volumes and is designed to help serve as a guide to states revising the provisions of their materials specifications to incorporate the use of recycled materials and industrial byproducts.Volume 1 is available in print and electronic versions. Volumes 2 to 8 are in electronic format only. The eight volumes are:Volume 1 Recycled Materials and Byproducts in Highway Applications—Summary ReportVolume 2 Coal Combustion ByproductsVolume 3 Non-Coal Combustion ByproductsVolume 4 Mineral and Quarry ByproductsVolume 5 Slag ByproductsVolume 6 Reclaimed Asphalt Pavement, Recycled Concrete Aggregate, and Construction Demolition WasteVolume 7 Scrap Tire ByproductsVolume 8 Manufacturing and Construction ByproductsA NCHRP Synthesis 435 website with links to all 8 volumes is available.
Keywords: Transportation and Infrastructure

Volumetric Requirements for Superpave Mix Design - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB's National Cooperative Highway Research Program (NCHRP) Report 567: Volumetric Requirements for Superpave Mix Design examines whether changes to the recommended Superpave mix design criteria for voids in mineral aggregate, voids filled with asphalt, and air voids content might further enhance the performance and durability of hot-mix asphalt.
Keywords: Transportation and Infrastructure

Fiber Additives in Asphalt Mixtures - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 475: Fiber Additives in Asphalt Mixtures summarizes the types of fibers used in asphalt mixtures, their properties, how they are tested, how they are applied, and lab and field performance of the fiber mixes.
Keywords: Transportation and Infrastructure

Understanding FAA Grant Assurance Obligations Volume 4: Summary of AIP Grant Assurance Requirements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Web-Only Document 44: Understanding FAA Grant Assurance Obligations Volume 4: Summary of AIP Grant Assurance Requirements contains a PowerPoint presentation summarizing the research conducted to develop a guidebook on Understanding FAA Airport Improvement Program (AIP) Grant Assurance Requirements. The results of this research include the Guidebook itself (Volume 1), Technical Appendices (Volume 2), which provides supplemental information on the requirements.Accompanying this volume, ACRP has released:ACRP Research Report 184: Executive Summary for the Guidebook on Understanding FAA Grant Assurance ObligationsWeb-Only Document 44 Vol. 1: Understanding FAA Grant Assurance Obligations - GuidebookWeb-Only Document 44 Vol. 2: Understanding FAA Grant Assurance Obligations - Technical AppendicesWeb-Only Document 44 Vol. 3: Understanding FAA Grant Assurance Obligations - Research ReportPowerPoint Slide File: Summary of AIP Grant Assurance Requirements
Keywords: Transportation and Infrastructure

Using Commodity Flow Survey Microdata and Other Establishment Data to Estimate the Generation of Freight, Freight Trips, and Service Trips: Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Freight Research Program (NCFRP) Research Report 37: Using Commodity Flow Survey Microdata and Other Establishment Data to Estimate the Generation of Freight, Freight Trips, and Service Trips: Guidebook provides policy makers with improved establishment-level models that estimate the Freight Trip Generation (FTG), the number of vehicle trips produced and attracted at a given establishment; the Freight Production (FP), the amount of cargo produced by the establishment; and the Service Trip Attraction (STA), and the number of vehicle trips that arrive at the establishment to perform a service activity. These models, estimated with the best data available, provide tools to assess the various facets of the overall Freight and Service Activity (FSA) that takes place in urban and metropolitan areas. The models will allow transportation practitioners to conduct sound curb-management, properly size loading and unloading areas, support traffic impact analyses, and improve transportation planning and management efforts.
Keywords: Transportation and Infrastructure

A Manual for Design of Hot-Mix Asphalt with Commentary - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 673: A Manual for Design of Hot-Mix Asphalt with Commentary incorporates the many advances in materials characterization and hot-mix asphalt (HMA) mix design technology developed since the conclusion of the Strategic Highway Research Program (SHRP).The final report on the project that developed NCHRP Report 673 and Appendixes C through F to NCHRP Report 673 were published as NCHRP Web-Only Document 159. The titles of the appendixes are as follows:• Appendix C: Course Manual• Appendix D: Draft Specification for Volumetric Mix Design of Dense-Graded HMA• Appendix E: Draft Practice for Volumetric Mix Design of Dense-Graded HMA• Appendix F: TutorialThe companion Excel spreadsheet HMA tool and the training course materials described in NCHRP Report 673 are available for download from the Internet.In January 2012, TRB released NCHRP Report 714: Special Mixture Design Considerations and Methods for Warm Mix Asphalt: A Supplement to NCHRP Report 673: A Manual for Design of Hot Mix Asphalt with Commentary. The report presents special mixture design considerations and methods used with warm mix asphalt.In January 2012, TRB released an errata to NCHRP Report 673: Page 41, Table 4-7, and page 123, Table 8-10, respectively, should be replaced with a new table.
Keywords: Transportation and Infrastructure

Statistical Modeling of Cement Heat of Hydration Using Phase and Fineness Variables - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 167: Statistical Modeling of Cement Heat of Hydration Using Phase and Fineness Variables explores alternative predictive models for seven-day cement heat of hydration.
Keywords: Transportation and Infrastructure

Recommended Practice for Stabilization of Sulfate-Rich Subgrade Soils - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 145: Recommended Practice for Stabilization of Sulfate-Rich Subgrade Soils examines the nature of minerals ettringite and thaumasite, and explores the mechanism of their formation in soils stabilized with lime, cement, or fly ash.
Keywords: Transportation and Infrastructure

Aggregate Properties and the Performance of Superpave-Designed Hot-Mix Asphalt - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 539: Aggregate Properties and the Performance of Superpave-Designed Hot-Mix Asphalt examines technical literature available since the conclusion of the Strategic Highway Research Program in 1993 on the impact of the aggregate properties specified by the Superpave mix design method on the performance of hot-mix asphalt. The performance of hot-mix asphalt (HMA) is largely determined by the characteristics of its constituents: asphalt binder and aggregate. In developing the Superpave mix design method, the Strategic Highway Research Program (SHRP, 1987–1993) targeted the properties of asphalt binders and HMA and their effects on pavement performance.
Keywords: Transportation and Infrastructure

Nondestructive Testing to Identify Delaminations Between HMA Layers, Volume 3 - Controlled Evaluation Reports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R06D-RW-3: Nondestructive Testing to Identify Delaminations Between HMA Layers, Volume 3 describes the controlled evaluations used in the development of nondestructive testing (NDT) techniques capable of detecting and quantifying delaminations in HMA pavements. SHRP 2 Report S2-R06D-RW-2 was developed as part of SHRP 2 Renewal Project R06D, which generated a sizable amount of documentation regarding the findings of evaluations and equipment development. The report for SHRP 2 Renewal Project R06D is therefore divided into five volumes. Volume 1 is a comprehensive summary of the study. Volumes 2 through 5 provide more detailed technical information and are web-only. The topics covered in other volumes are listed below.Volume 2: Theoretical ModelsVolume 4: Uncontrolled Evaluation ReportsVolume 5: Field Core VerificationRenewal Project R06D also produced a Phase 3 Report to document guidelines for use of ground penetrating radar and mechanical wave nondestructive technologies to detect delamination between asphalt pavement layers.
Keywords: Transportation and Infrastructure

Microsurfacing - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 411: Microsurfacing explores highway microsurfacing project selection, design, contracting, equipment, construction, and performance measurement processes used by transportation agencies in the United States and Canada.Microsurfacing is a polymer-modified cold-mix surface treatment that has the potential to address a broad range of problems on today’s highways.
Keywords: Transportation and Infrastructure